Shifting Italian masculinities: insights from three male performances in festival of Sanremo 2022 - Antonelli, Carlotta (Ámbitos. Revista Internacional de Comunicación, 2023)
The Festival of Sanremo is arguably one of the biggest events on Italian television in terms of audience and prestige. It sits within complex socio-cultural dynamics and can be understood only through a lens that focuses on the ecology of Italian media and values songs as cultural objects (Tomatis, 2016). Indeed, acts happening on Sanremo’s stage can acquire a special significance in terms of their potential resonance (Facci et al., 2011) and the festival has often been used to spread political messages or raising awareness about social issues. In recent years, the festival has featured singers whose performances and character increasingly challenge and complicate traditional expressions of gender, with mixed, often polarized, receptions. The artistic choices of Amadeus (host of the 2019 through 2024 editions) and the authors reflect the trend of assimilation into the mainstream of queer or otherwise gender-defying signifiers in audiovisual pop productions (Ferrante, 2019). To zoom in on these processes, we draw our attention to performances of masculinities (Butler, 1990 & 2004; Connell, 2020; Feasey, 2008; Reeser, 2011) in the context of the 2022 edition of Sanremo. We will operate a visual analysis (Aubrey & Frisby, 2011; Russmann & Svensson, 2016; Tiindenberg & Baym, 2017) of the opening performances of three male artists, identifying three different ways of performing masculinity on the stage: Rkomi, Achille Lauro and Michele Bravi.